PENGARUH KUALITAS PELAYANAN, HARGA DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN PASCA PANDEMIC COVID (Studi pada Konsumen di Sardo Swalayan Kota Malang) - Arrum, Insyanin Qamilia; Saroh, Siti; Trianti, Khoiriyah (Transpublika Publisher, 2023)
This study aims to assess the impact of service quality, price, and location on purchasing decisions following the Covid pandemic. It employs a quantitative, correlational approach, with data gathered through a Likert scale questionnaire. The sample consists of 100 students as customers of Sardo Swalayan in Malang City. Data analysis involves classical assumption testing and hypothesis testing. Consumer purchasing decisions are positively influenced by service quality, validating the first hypothesis. There is an essential and positive effect of price on purchasing decisions, thus the second hypothesis is accepted. Customers of Sardo Swalayan in Malang City consider location as a crucial factor in their purchasing decisions. The fourth hypothesis is accepted after partial and simultaneous testing, as service quality, price, and location are factors affecting consumer purchasing decisions at Sardo Swalayan in Malang City. This study is intended to serve as a reference for Sardo Swalayan in Malang City to maintain its service quality, as this can encourage consumers to make purchases and potentially become loyal customers, thus increasing the profitability of Sardo Swalayan in Malang City.